A Review Study of Critical Oxygen Content to Stress Corrosion Cracking of Stainless Steel 304 - Ismail, Azzura; Aubergine Trisha Lim (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Stress corrosion cracking is so destructive that it can cause severe damage to a component to the point of beyond repair thus the purpose of this research is to investigate the critical oxygen content to stress corrosion cracking to stainless steel 304. The objectives of this study are to determine the corrosion rate of the experimental immersion, to study the effect of temperature to the length of immersion period, to investigate the effect of oxygen in accelerating the corrosion rate and to compare the result if the corrosion rate of experimental immersion and the reviewed electrochemical test. The investigation is done by conducting an immersion test and reviewing previous research. Based on the immersion experiment, the higest corrosion rate was recorded on the 45° U-bend specimen. From the previous immersion research, it was found that the temperature plays an important role in accelerating the corrosion rate. A review of Tafel analysis was conducted for the electrochemical test and the outcome was the longer the specimen immersed in the electrolyte, the higher the corrosion rate. This is due to the presence of the oxygen that accelerate the rate of corrosion. A comparison of corrosion rate was made between the experimental immersion and the reviewed tafel analysis. The result shows similar trend which is the longer the period of immersion, the higher the corrosion rate.